2021
DOI: 10.1080/15487733.2021.1946297
|View full text |Cite
|
Sign up to set email alerts
|

Online conferencing in the midst of COVID-19: an “already existing experiment” in academic internationalization without air travel

Abstract: Academia, as many other sectors, has faced wide-ranging disruptions due to COVID-19, with teaching and research activity conducted entirely online in many countries. Before the pandemic grounded travel, academics were often hypermobile, some traveling more than 150,000 kilometers per year for conferences, board meetings, collaborations, fieldwork,seminars, and lectures. It is no surprise then that academic flying is among the leading causes of universities' greenhouse-gas (GHG) emissions. Despite growing aware… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…These findings are well in line with our descriptive analysis in section 5.1.4. where we showed that the most influential factor in decreasing business air travel was reported as “the ability to conduct meetings through videoconference” by the respondents during the pandemic. This finding also can be supported by the previous research ( Jack & Glover, 2021 ), and not surprisingly, our model suggests the effect of adopting virtual meetings is likely to transcend the pandemic era.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…These findings are well in line with our descriptive analysis in section 5.1.4. where we showed that the most influential factor in decreasing business air travel was reported as “the ability to conduct meetings through videoconference” by the respondents during the pandemic. This finding also can be supported by the previous research ( Jack & Glover, 2021 ), and not surprisingly, our model suggests the effect of adopting virtual meetings is likely to transcend the pandemic era.…”
Section: Resultssupporting
confidence: 91%
“…They used the PLS-SEM approach and showed that trust, habit, social norms, and perceived risk are the significant antecedents of travel intention. Moreover, Jack & Glover, (2021) reported that online conferencing amid Covid-19 remarkably reduced air travel among academics who were frequent travelers, and some of them used to travel more than 150,000 km each year to attend conferences and workshops.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They also find it difficult to start collaborative projects in a digital environment without having met in person before. However, Jack and Glover (2021) observe that digital tools can allow for networking opportunities when event organisers make a deliberate effort to facilitate by design. For example, by matching participants by research interests and letting them meet in break out rooms or a one‐on‐one video call.…”
Section: Discussionmentioning
confidence: 99%
“…The conference schedule was thus divided into three major regions based on time zone (an oversimplification driven by necessity to fit within the Japanese time zone of the organizers (Japan Standard Time, JST)): East Asia/Oceania, Middle East/Europe, and The Americas. Each scientific session was scheduled to include two of these regions, so as to not marginalize attendees from specific time zones (which is an issue of noninclusivity of many digital meetings (Jack and Glover, 2021)). Optimally, this meant that the conference would consist of three sessions spread out over the 24 h day, but the decision was made to optimize for the organizers hosting and running the event who were based in Japan, resulting in two scientific sessions per day (Tables 1 and 2).…”
Section: Meeting Schedulementioning
confidence: 99%